EXPERIMENTAL INVESTIGATION OF A CONCEPT WAVE ENERGY CONVERTER FOR HARNESSING LOW AMPLITUDE SEA WAVES - OLAKUNLE KAYODE; TITUS OLUWASUJI AJEWOLE; OLUFEMI ADEBOLA KOYA (Journal of Engineering Studies and Research)
This paper presents the results from experimental validation of numerical simulation of a concept wave energy converter for low amplitude sea waves. The device was conceived to contain a wave amplifying device (WAD) to magnify the wave height of incident waves while point absorber buoy(s) efficiently harness the wave energy for electricity production. The validation results show that the optimum aperture angle for the WAD is 45±2 degree, and wave height magnification of 170% is possible. The optimal buoy shape for the device was confirmed as concave wedge buoy. The combination of the two in a single device shall make economical the harnessing of low amplitude waves.